Empirical evidence on return migration from Spain to Ecuador. Discourse, myth or reality? - Moreno-Márquez, Gorka; Álvarez-Román, José (Papeles de Población; Vol. 23 Núm. 91 (2017), 2017)
The purpose of this article is to provide an in-depth analysis of the phenomenon of international return migration. To this end different statistical sources are analysed and several in-depth interviews conducted in order to quantify the scale of the return migration taking place in the population of Ecuadorian origin resident in Spain. Starting from this premise, we can emphasise that the phenomenon of return migration to Ecuador, although it has increased appreciably in recent years as a consequence of the economic crisis in Spain, is not proving to be massive. This assertion poses the need for reflecting on the return policies that have been implemented to date and on what the priorities should be in both the country of origin and the receiver country when protecting and providing support to the international migrant population.